Practice-theoretical possibilities for social marketing: two fields learning from each other. Issue 2 (10th April 2017) - Spotswood, Fiona; Chatterton, Tim; Morey, Yvette; Spear, Sara
Abstract : Purpose: This paper aims to introduce key concepts from practice theory (PT) to the social change agenda and draw on the unique contributions of the social marketing field. PT has underpinned a growing stream of research in pro-environmental studies seeking to reduce impacts of particular behaviours, but it remains theoretical. By drawing on social marketing's applied roots, this paper introduces a practice-theoretical intervention planning process (P-TIPP) which frames the unique contribution of social marketing in behaviour change and foregrounds practice- not individual-level change. Design/methodology/approach: The P-TIPP draws on the total process planning model, introducing the concept of "practice as entity" and "practice as performance" to frame intervention planning tasks. The process locates the contribution of social marketing within a transdisciplinary framework which emphasises transforming collective conventions. Findings: This is a conceptual paper, but the possibility for PT to make a significant contribution to the world of social marketing is outlined. Research limitations/implications: P-TIPP is untested. Also, practices can be difficult to identify and somewhat abstract. Finally, it can be challenging to introduce the approach to policy, funding and practitioner procedures. Practical implications: The implications of P-TIPP are that social change interventions are devised, underpinned and planned using insights from PT, such as the way behavioural patterns fit into broader understandings of practice. The subsequent social change agenda will be inherently transdisciplinary, sustainable and reduce focus on individual power to change. Originality/value: This paper is a first attempt at exploring what PT, and social marketing can learn from each other for the future effectiveness of social change activity.